Analisis Biaya dan Waktu Optimal pada Proyek Ruko Paskal Hypersquare dengan Least Cost Scheduling - Adianto, Yohanes L.D.; Maliki, Ali; Prasetyo, Wisnu (Department of Civil Engineering, Diponegoro University, 2006)
So many construction projects had been done without optimal project cost and optimal project time completion. Time needed for project completion actually can be shortened with using more economical resources. This paper will try to analyze how to get an optimal project cost and optimal project time completion. This is a case study of Paskal Hypersquare Ruko project which is located at Pasir Kaliki Street, Bandung. Analysis will be done on structural works and wall fixing, both activities will be accelerated using overtime work schedule on critical works. All will be done in accordance with worker's coefficient standard which is set by Dinas Tata Ruang dan Permukiman Jawa Barat for year 2004, and also in accordance with worker's pay standard issued by Jurnal Bahan Bangunan Jawa Barat year 2004 edition. From 21 acceleration alternatives which were analyzed, finally found the most optimal project alternative. With this alternative, the project can be completed in 158 days with a total project cost Rp 31.658.654.555,00. As conclusion, this optimal alternative will save cost as much as Rp 14.831.515,00 and shortened the completion time 7 days earlier. Keywords: least cost scheduling, time, cost, optimal project cost, project accelerationPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3931[How to cite: Adianto, Y.L.D., Maliki, A. dan Prasetyo, W., 2006, Analisis Biaya dan Waktu Optimal pada Proyek Ruko Paskal Hypersquare dengan Least Cost Scheduling, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 21-29]